2012
DOI: 10.1093/nar/gks1340
|View full text |Cite
|
Sign up to set email alerts
|

Genes involved in host–parasite interactions can be revealed by their correlated expression

Abstract: Molecular interactions between a parasite and its host are key to the ability of the parasite to enter the host and persist. Our understanding of the genes and proteins involved in these interactions is limited. To better understand these processes it would be advantageous to have a range of methods to predict pairs of genes involved in such interactions. Correlated gene expression profiles can be used to identify molecular interactions within a species. Here we have extended the concept to different species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
(52 reference statements)
0
22
0
Order By: Relevance
“…Then the parasites need to escape the host defence to proliferate and transmit. Host–parasite interactions are studied from genotype host –genotype parasite level and correlated gene expression level (Tierney et al ., ; Reid and Berriman, ; Barribeau et al ., ). In our study, two clusters of genes showed co‐expression within both host and parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Then the parasites need to escape the host defence to proliferate and transmit. Host–parasite interactions are studied from genotype host –genotype parasite level and correlated gene expression level (Tierney et al ., ; Reid and Berriman, ; Barribeau et al ., ). In our study, two clusters of genes showed co‐expression within both host and parasite.…”
Section: Discussionmentioning
confidence: 99%
“…Since STRING software until date only accepts A. gambiae data, orthologues from A. stephensi obtained sequences were used 7, 64 . Briefly, the program by single protein name or amino acid sequence generates the network images based on a spring model.…”
Section: Methodsmentioning
confidence: 99%
“…Such investigations provide new information as to how the parasite responds to changes in its microenvironment, particularly within the host, and how the host immune system reacts to the presence of the pathogen [27]. While many studies have sought to examine the response of the host to an active infection [28][29][30][31][32][33][34], this review will focus on the schistosome parasite itself and the transcriptional changes that allow it to survive long term within the host.…”
Section: Rnai As a Tool To Investigate Schistosome Biologymentioning
confidence: 99%